Physiological and Behavioral Responses of Sohagi Ewe Lambs Exposed to Direct Sunlight Under Subtropical Climatic Conditions - Elaref, M. Y.; Solouma, G. M.; Abdel-latef, D. A. (Tropical Animal Science Journal, 2022)
This study aimed to assess the ability of Sohagi ewe lambs to adapt to heat stress conditions during the summer season in arid regions of Sohag governorate, Egypt. Twenty-one Sohagi ewe lambs (9-11 months old and 25.55±2.69 kg average body weight) were divided into three equal groups. In the 1st group, ewe lambs were housed in an indoor barn and considered as control (DS0), while those in the 2nd and 3rd groups were daily exposed to direct sunlight in the outdoor barns for 4 hours (DS4) and 8 hours (DS8), respectively. Physiological, blood parameters, and daily behavioral activities of each animal in experimental groups were obtained and data were analyzed in a completely randomized design. Results showed that rectal temperature, respiration rate, and water consumption of Sohagi ewe lambs in DS4 and DS8 groups increased significantly (p